Rights of Migrants: Notes on the Jurisprudence of the Inter-American Court of Human Rights (2011)
The rights of migrants represent a challenge for States, because their guarantee evidences the permanent tension between the sovereignty of the States and the protection of human rights in the international context. This article will analyse if it is really possible to affirm the existence of a true evolutionary development of the jurisprudence of the Inter-American Court of Human Rights in a contentious and consultative way and which, therefore, may contribute to the improvement of the rights of migrants in the IACHR. To this end, the text will address the following parts: I) Regulatory framework oriented to the sovereignty of States; II) The progressive contentious jurisprudence of the Inter-American Court III) The advisory opinions: integrating elements of rights and; IV) Conclusions.